2008
DOI: 10.1177/1933719108318598
|View full text |Cite
|
Sign up to set email alerts
|

Combination of CCR1 mRNA, MCP1, and CA125 Measurements in Peripheral Blood as a Diagnostic Test for Endometriosis

Abstract: This study investigated the possible use of CCR1 mRNA measurement in peripheral blood leukocytes in combination with measurements of monocyte chemotactic protein-1 (MCP-1) and CA125 protein in serum as a diagnostic test for endometriosis.The expression of CCR1 mRNA in peripheral blood leukocytes was measured by quantitative real-time polymerase chain reaction. MCP-1 and CA125 levels in serum were determined by ELISA and ECLIA.The ratio of CCR1/HPRT mRNA in peripheral blood of patients with endometriosis and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 27 publications
(30 reference statements)
1
42
0
6
Order By: Relevance
“…Different serum markers have been established that may identify patients in the initial stages of endometriosis, when ablation or excision of lesions improves reproductive outcomes (11)(12)(13)(14)(15)(16)(17)(18). Among these markers, IL-6 appears to present good discriminatory power (11,14,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different serum markers have been established that may identify patients in the initial stages of endometriosis, when ablation or excision of lesions improves reproductive outcomes (11)(12)(13)(14)(15)(16)(17)(18). Among these markers, IL-6 appears to present good discriminatory power (11,14,17).…”
Section: Introductionmentioning
confidence: 99%
“…Among these markers, IL-6 appears to present good discriminatory power (11,14,17). In turn, other studies have demonstrated that combined analyses of different serum markers may improve the accuracy of endometriosis diagnosis (12,13,15,16,18), however no highly accurate marker for endometriosis has yet been detected. Therefore, the present study aimed to evaluate IL-6 levels in serum and PF, as well as IL-6 gene expression in subcutaneous and visceral fat, and in the eutopic and ectopic endometrium of patients with pelvic endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…The Definitive diagnosis of endometriosis can only be achieved visually via Laparoscopy. Although non invasive methods for detecting endometriosis are currently under developed, such as the CA125 Antigen [13], Ultrasound scanning [14], and endometrium nerve density [15]. For this reason 8 patients were excluded from our study because they had other pathology rather than endometriosis at laparoscopic management.…”
Section: Discussionmentioning
confidence: 99%
“…Although non-invasive methods for detecting endometriosis are currently under developed, such as the CA125 Antigen [13], ultrasound scanning [14], and endometrial nerve density [15], there are various methods of treatment for Endometriosis, Medical and Surgical (Open or Laparoscopy). Endometriosis is considered as an estrogen dependent disorder, therefore current medical therapies are centered upon lowering circulating estrogen levels.…”
Section: Introductionmentioning
confidence: 99%
“…qRT-PCR has already been shown to be a promising diagnostic tool in peripheral blood of patients with endometriosis [34,35]. In our study, we used qRT-PCR to test if mRNA of genes known to play a pivotal role in the invasive process of local implantation and development of endometriotic lesions might be blood markers of endometriosis.…”
Section: Introductionmentioning
confidence: 99%